2023
DOI: 10.1111/nph.18848
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effector profiles between bacterial colonisers of kiwifruit reveal redundant roles converging on PTI‐suppression and RIN4

Abstract: Testing effector knockout strains of the Pseudomonas syringae pv. actinidiae biovar 3 (Psa3) for reduced in planta growth in their native kiwifruit host revealed a number of nonredundant effectors that contribute to Psa3 virulence. Conversely, complementation in the weak kiwifruit pathogen P. syringae pv. actinidifoliorum (Pfm) for increased growth identified redundant Psa3 effectors.Psa3 effectors hopAZ1a and HopS2b and the entire exchangeable effector locus (DEEL; 10 effectors) were significant contributors … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…It will be interesting to test in future work whether the interaction of the HopZ5:AcRIN4-2:NbPTR1a complex could be detected using a yeast three-hybrid system. Jayaraman et al 20 found that four out of five key redundant Psa3 effectors collectively essential for full Psa3 virulence probably targeted host RIN4 proteins (HopZ5a, AvrPto1b, AvrRpm1a, and HopF1e). Since only HopZ5 appears to be responsible for Nb PTR1a -conferred immunity against Psa3, this is probably further evidence that RIN4 itself may not be the host protein directly guarded by PTR1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It will be interesting to test in future work whether the interaction of the HopZ5:AcRIN4-2:NbPTR1a complex could be detected using a yeast three-hybrid system. Jayaraman et al 20 found that four out of five key redundant Psa3 effectors collectively essential for full Psa3 virulence probably targeted host RIN4 proteins (HopZ5a, AvrPto1b, AvrRpm1a, and HopF1e). Since only HopZ5 appears to be responsible for Nb PTR1a -conferred immunity against Psa3, this is probably further evidence that RIN4 itself may not be the host protein directly guarded by PTR1.…”
Section: Discussionmentioning
confidence: 99%
“…In soybean, RIN4 modification is involved in the recognition of AvrB and AvrRpm1 by Rpg1b and Rpg1r, respectively 19 . Recently, Jayaraman et al 20 found that five pathogenicity-associated Psa biovar 3 effectors (HopZ5a, HopH1a, AvrPto1b, AvrRpm1a, and HopF1e) are collectively essential for full Psa3 virulence and that they largely target host RIN4 proteins. Although most Psa T3Es have been identified, we have yet to fully uncover which NLR proteins are responsible for recognizing and responding to specific effectors during ETI.…”
Section: Introductionmentioning
confidence: 99%
“…Callose deposit quantification assays were conducted and images acquired as previously described in Jayaraman et al (2023). Images were analysed using ImageJ software by determining the average area of a single callose deposit and then callose counts calculated based on total callose deposit area in each image.…”
Section: Methodsmentioning
confidence: 99%
“…The Psa3 V-13 complete effector knockout strain was generated using the pK18mobsacB-based vectors used previously to generate single knockout strains (Hemara et al, 2022; Jayaraman et al, 2023). The single effectors or effector blocks were sequentially knocked out to generate the 33 effector knockout strain (Psa3 V-13 Δ 33E ) in the order: hopZ5a/hopH1a ( using the hopZ5a/hopH1a double knockout vector ), hopBP1a ( previously hopZ3), hopQ1a, hopAS1b, avrPto1b ( previously avrPto5), avrRpm1a, fEEL (avrD1/avrB2b/hopF4a/hopAW1a/hopF1e/hopAF1b/hopD2a/hopF1a), hopF1c ( previously hopF2), hopD1a ( using the hopQ1a/hopD1a double knockout vector ), CEL (hopN1a/hopM1f/avrE1d), hopR1b, hopAZ1a, hopS2b, hopY1b, hopAM1a-1, hopAM1a-2, hopBN1a, hopW1c (previously hopAE1), hopAU1a, hopI1c , and hopAH1 block (hopAG1f/hopAH1c/hopAI1b ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation